Survey of Physical Fitness Levels for Grade 1 and 2 Elementary School Students in Brengkok Village, Brondong District, Lamongan Regency in 2022/2023 - Reo Prasetiyo Herpandika; M. Anis Zawawi; Ahmad Nurdin (CV. Nusantara Sporta, 2023)
The results of observations in elementary schools grades 1-2 in Brengkok Village, Brondong District, Lamongan Regency, as many as 119 students, Physical Education teachers have never conducted physical fitness tests on their students, due to a lack of facilities and infrastructure and some have said that for years only familiar with the Indonesian Physical Fitness Test (TKJI), and found no other fitness tests required by students. The formulation of the problem in this study is: 1) What is the Physical Fitness Level of Class 1 and 2 Students in Every Elementary School Institution in Brengkok Village, Brondong District, Lamongan Regency? 2) How is the Physical Fitness Level of Grade 1 and 2 Elementary School Students in Brengkok Village, Brondong District, Lamongan Regency?. This study uses a quantitative approach with a survey method description technique. The sample of this study were 119 students in grades 1 and 2 of elementary schools in Brengkok Village, Brondong District, Lamongan Regency, using a purposive sampling technique. The instrument used was the Indonesian Student Fitness Test (TKSI) Phase A. The results of this study indicated that the level of physical fitness of grade 1 and 2 elementary school students in Brengkok Village, Brondong District, Lamongan Regency received the Very Good Category 8 students (7%), Good 63 students (53%), Moderate 47 students (39%), Less 1 student (1%), Very Less 0 students (0%), so it is in the Good category